(untitled) (World Economics and Finance Bulletin, 2022)
The article discusses the role of the digital economy in the development of society, the current role of information platforms and digital enterprises, legal and institutional changes in the transition to e-government in Uzbekistan, the impact of the Digital Uzbekistan 2030 Strategy in the economy, social sphere and public administration